Surgical stress response following hip arthroplasty regarding choice of anesthesia and postoperative analgesia - Kendrišić, Mirjana L; Šurbatović, Maja; Djordjević, Dragan; Jevdjić, Jasna (Vojnosanitetski pregled, 2018)
Background/Aim. Significant surgical stress response consisting of hormonal, metabolic and inflammatory changes can be initiated by the hip replacement surgery. Appropriate choice of anesthesia and postoperative analgesia should provide diminution of surgical stress response and may reduce number of perioperative complications. Surgical stress response after peripheral nerve blocks has not been studied extensively in patients who underwent hip replacement. The aim of the study was to investigate whether continuous lumbar plexus block can significantly reduce surgical stress response in comparison to other types of postoperative analgesia – continuous epidural analgesia and intravenous patient controlled analgesia (PCA) with morphine. Methods. Prospective study included 60 patients, scheduled for total hip arthroplasty. The patients were randomized into 4 groups: group CNB (central nerve block - epidural), group PNB (Peripheral nerve block - lumbar plexus block), SAM (Spinal anesthesia- PCA (anesthesia) morphine) and GAM (General anesthesia + PCA with Morphine). Serum levels of cortisol, thyroid hormones (T3, T4) and thyroid stimulating hormone (TSH), insulin, glucose and C-reactive protein (CRP) were measured in all groups – preoperatively, as well as 4 h, 12 h and 24 h after surgery. Results. The study showed that average serum cortisol levels were significantly lower 4 h after the operation in the groups where methods of regional anesthesia were performed intraoperatively (SAM, CNB, PNB); (F = 19.867; p < 0.01). Groups with postoperative continuous catheter analgesia (CNB, PNB) had significantly lower serum cortisol levels 12 h after the operation (F = 8.050; p < 0.01). The highest serum insulin levels were detected 4 h postoperatively in the CNB and PNB group, while the lowest were in the GAM group (F = 5.811; p < 0.05). Twelve hours after the operation, the lowest values of insulin were measured in the SAM group (F = 5.052; p < 0.05), while 24 h postoperatively, the lowest values were found in the SAM and GAM group (F = 6.394; p < 0.05). T3, T4 and TSH levels showed slight reduction in comparison to preoperative values without statistical significance. Blood glucose levels were significantly different among the groups 4 h after surgery with the highest values recorded in the GAM group and the lowest ones in the SAM group (F = 10.084; p < 0.01). On the other hand, 12 h after the operation significant rise in blood glucose levels was detected in the SAM group (F = 7.186; p < 0.01) Levels of CRP increased remarkably 12 h and 24 h after the surgery, but without significant difference among the groups. Conclusion. Administration of postoperative analgesia using continuous lumbar plexus block following hip arthroplasty reduces significantly stress response in comparison to postoperative PCA with morphine and has comparable effects on hormone release to epidural analgesia. Spinal anesthesia provides the best diminution of surgical stress response in the early postoperative period in comparison with other types of intraoperative analgesia.